THE INFLUENCE OF ACHIEVEMENT MOTIVATION AND ACADEMIC SELF-EFFICACY ON SPEAKING PROFICIENCY - Yuni Astuti (Magister Scientiae, 2019)
This quantitative study employs a correlational design that is to find out the relationship among achievement motivation, academic selfefficacy and the students’ speaking performance. Two questionnaires with four likert-scale were used to measure the students’ level in this study. Based on the result of the data analysis about the relationship among the variables, some points could be concluded. First, there was a significant average positive correlation between achievement motivation level and the students’ speaking performance level (r = .688, sig. = .00). Second, the correlation between academic self-efficacy level and the students’ speaking performance level was a significant moderate positive correlation (r =. 691, sig. = .00). Third, the relationship between achievement motivation combined with academic self-efficacy and the students’ speaking performance was statistically a significant high positive correlation since The result was significant (r= 0.737, sig. = .00). It was concluded that the teachers should be closer to the students in order to build more academic self-efficacy beliefs of the students. Teachers are expected to encourage the students to be more open and share their difficulties in learning especially in the speaking class. Thus, by having close communication between teachers and the students, it is expected that the students’ problems during the learning process can be solved. The students’ achievement motivation and the students’ academic self-efficacy are expected to be higher and stronger in completing the course with high achievement.